Neuropeptide F neurons modulate sugar reward during associative olfactory learning of Drosophila larvae. - Rohwedder, A.; Selcho, M.; Chassot, B.; Thum, A.S. (Journal of Comparative Neurology, 2015)
All organisms continuously have to adapt their behavior according to changes in the environment in order to survive. Experience-driven changes in behavior are usually mediated and maintained by modifications in signaling within defined brain circuits. Given the simplicity of the larval brain of Drosophila and its experimental accessibility on the genetic and behavioral level, we analyzed if Drosophila neuropeptide F (dNPF) neurons are involved in classical olfactory conditioning. dNPF is an ortholog of the mammalian neuropeptide Y, a highly conserved neuromodulator that stimulates food-seeking behavior. We provide a comprehensive anatomical analysis of the dNPF neurons on the single-cell level. We demonstrate that artificial activation of dNPF neurons inhibits appetitive olfactory learning by modulating the sugar reward signal during acquisition. No effect is detectable for the retrieval of an established appetitive olfactory memory. The modulatory effect is based on the joint action of three distinct cell types that, if tested on the single-cell level, inhibit and invert the conditioned behavior. Taken together, our work describes anatomically and functionally a new part of the sugar reinforcement signaling pathway for classical olfactory conditioning in Drosophila larvae. J. Comp. Neurol. 523:2637-2664, 2015. © 2015 Wiley Periodicals, Inc.